COMPARISON OF EARNINGS MANAGEMENT IN EACH NON-FINANCIAL SECTOR OF BUMN LISTED ON THE IDX - Shintya Fransiska (JOURNAL OF ACCOUNTING, ENTREPRENEURSHIP AND FINANCIAL TECHNOLOGY (JAEF), 2021)
This research was conducted to determine whether there are differences in each non-financial sector of BUMN listed on the IDX in carrying out earnings management practices. The research sample includes a saturated sampling method. The research sample consisted of 19 companies were divided into 8 sectors. The amount of data used is 225 data from 2006-2019. Earnings management will be measured using discretionary accruals with a Modified Jones model. The hypothesis was tested using the Kruskal Wallis test and followed by the Dunn test. The results show that there are differences in the level of earnings management in each non-financial sector of BUMN listed on the IDX. The difference is due to the higher level of earnings management carried out by the construction sector compare to the other sectors. Furthermore, the metal sector has the lowest average level of earnings management practices.